Asking bigger questions: An invitation to further conversation - Bloch-Schulman, Stephen; Conkling, Susan Wharton; Linkon, Sherry Lee; Manarin, Karen; Perkins, Kathleen (Teaching and Learning Inquiry, 2016)
In this essay, the editors and contributors to this special section on SoTL in the Arts and Humanities argue that given the current climate and context, debates within SoTL about appropriate methodology both lead scholars from their disciplines to reject SoTL and also, more importantly, distract us from more significant questions and challenges. If, instead, SoTL would embrace not only its diversity but also its political potential, then we, as a scholarly community, would be in a position to do more than merely improve students’ learning in our own classrooms. We could help to transform higher education. To achieve that, we need a broader conversation and a wider range of studies. We also need to be mindful of and engaged with the political, economic, and ideological forces that are shaping our institutions, our work, and our students’ expectations.